A novel germ cell protein, SPIF (sperm PKA interacting factor), is essential for the formation of a PKA/TCP11 complex that undergoes conformational and phosphorylation changes upon capacitation. Issue 8 (22nd April 2016) - Stanger, Simone J.; Law, Estelle A.; Jamsai, Duangporn; O'Bryan, Moira K.; Nixon, Brett; McLaughlin, Eileen A.; Aitken, R. John; Roman, Shaun D.
ABSTRACT: Spermatozoa require the process of capacitation to enable them to fertilize an egg. PKA is crucial to capacitation and the development of hyperactivated motility. Sperm PKA is activated by cAMP generated by the germ cell‐enriched adenylyl cyclase encoded by Adcy10 . Male mice lacking Adcy10 are sterile, because their spermatozoa are immotile. The current study was designed to identify binding partners of the sperm‐specific (Cα2) catalytic subunit of PKA (PRKACA) by using it as the "bait" in a yeast 2‐hybrid system. This approach was used to identify a novel germ cell‐enriched protein, sperm PKA interacting factor (SPIF), in 25% of the positive clones. Homozygous Spif ‐null mice were embryonically lethal. SPIF was coexpressed and coregulated with PRKACA and with t‐complex protein (TCP)‐11, a protein associated with PKA signaling. We established that these 3 proteins form part of a novel complex in mouse spermatozoa. Upon capacitation, the SPIF protein becomes tyrosine phosphorylated in >95% of sperm. An apparent molecular rearrangement in the complex occurs, bringing PRKACA and TCP11 into proximity. Taken together, these results suggest a role for the novel complex of SPIF, PRKACA, and TCP11 during sperm capacitation, fertilization, and embryogenesis.—Stanger, S. J., Law, E. A., Jamsai, D., O'Bryan, M. K., Nixon, B., McLaughlin, E. A., Aitken, R. J., Roman, S. D. A novel germ cell protein, SPIF (sperm PKA interacting factor), is essential for the formation of a PKA/TCP11 complex that undergoes conformational and phosphorylation changes upon capacitation. FASEB J. 30, 2777‐2791 (2016). www.fasebj.org